LEGAL STUDY OF THE AUTHORITY OF THE MEDAN HIGH COURT IN CORRECTING CRIMINAL DECISIONS IN DOMESTIC VIOLENCE CASES - Sempati Uli Artha Tambunan; Tika Hairani; Aulia Rahman Hakim Hasibuan (PT. Sinergi Legal Publisher, 2025)
What is desired by couples in a marriage is to form a family that is able to provide eternal happiness and create harmony and peace in addition to having children in accordance with Law Number 1 of 1974 concerning Marriage. Domestic violence (KDRT) is a form of violence that has characteristics that occur in the home environment, involving family members as perpetrators and victims. However, domestic neglect of wives still often occurs, although various efforts have been made to reduce and even overcome it. Based on this, the problem arises of what factors cause domestic neglect and how to punish perpetrators of domestic violence. Therefore, research is needed, namely the type of empirical legal research. In this case, the law is conceptualized as an empirical symptom that can be observed and studied in the field. The factors that cause domestic neglect are economic problems, infidelity and behavioral factors. The problem of punishment from the analysis of cases of domestic neglect that were raised was the imposition of a criminal sentence on the defendant with a very light 6-month prison sentence. Regarding the elimination of domestic violence, this is regulated in Law Number 23 of 2004.